Topical treatment of blue-green algae extract promote healing of diabetic wound. - Fakurazi, Sharida; Arulselvan, Palanisamy; Pauzi, Aimi Syarina; Govindarajan, Karthivashan; Abbas, Faridah; Cheah , Pike See (2013)
Diabetes is a global endocrine disorder imposes economic burden on national health care systems and affects millions of people worldwide. Diabetic foot ulcers are a serious secondary complication of diabetes, and precede 84% of all diabetes related lower leg amputations. Impaired wound healing is a substantial problem in diabetes, The wound is often resistant to conventional wound management and may ultimately threaten limb viability. Blue-green algae (Spirulina platensis) is gaining more attention and becoming a health food worldwide due to its nutritional and medicinal properties. Their roles as antioxidant, antiviral, anticancer and antidiabetic have been well established, The aim of this study is to examine the efficacy of aqueous extract of Spirulina platensis on wound repair in streptozotocin-nicotinamide induced diabetic rats. Open excision wounds were made on the back of rats 5 days after diabetes induction, Aqueous extract at a dosage of 100 and 200 mg/kg b.wt was reconstituted in 100 ul of PBS and applied topically once every 2 days up to 14 days to the wounds, Animals in normal and diabetic control groups were left untreated. Wound areas were measured on day 0, 7 and 14 post-wounding, Extract treated animals exhibited 73% and 79% of percentage wound contraction, when compared to diabetic control which was 48% on day 14, The healing rate of extract treated wounds increased significantly as compared to diabetic control. The findings demonstrate the beneficial effects of the topical application of blue-green-algae aqueous extract in the acceleration of diabetic wound healing in animal model.